Identify texture of MRI human brain using Adaptive Fuzzy C-Means (AFCM) Algorithm / Faridatul Akma Mohd Noor - Faridatul Akma, Mohd Noor (2010)
In the past few years, segmentation and classification techniques for identify texture has been implemented in many areas especially in human brain. The method for identify texture of human brain is a great help for medical analysis. The result of this research can be uses for segmentation and classification process. To access its viability, a prototype with interactive graphical user interface (GUI) was developed and tested for its reliability. The main objective of this research is to develop a prototype that use Adaptive Fuzzy C-Means (AFCM) algorithm to identify texture of human brain.